Half car suspension system using fuzzy logic controller - Basari, Amat Amir; Esro, Mazran; Abdul Manap, Redzuan (2011)
The purpose of this paper is to present a new method in modeling an active suspension system for a half-car model in state space form and to develop a robust control strategy in controlling the active suspension system. Fuzzy logic is used to control the system. Velocity and displacement of the front wheels are taken as input data of the fuzzy logic controller. Active forces improving vehicle driving, ride comfort and handling properties are considered to be the controller outputs. The controller design is proposed to minimize chassis and wheels deflection when uneven road surfaces, pavement points, etc. are acting on the tires of running cars. Comparison of performance of active suspension fuzzy control system with passive suspension system is shown using Matlab/Simulink simulation. From analysis, it shows that active system has better performance than the passive system.